ICAMs are dispensable for influenza clearance and anti-viral humoral and cellular immunity - Kozlovski, Stav; Regev, Ofer; Sapoznikov, Anita; Kizner, Marina; Achdout, Hagit; Petrovich-Kopitman, Ekaterina; Elkahal, Jacob; Addadi, Yoseph; Silva Castanheira, Fernanda Vargas E.; Feigelson, Sara W.; Kubes, Paul; Erez, Noam; et al. (Frontiers in Immunology, 2023)
αLβ2 (LFA-1) mediated interactions with ICAM-1 and ICAM-2 predominate leukocyte-vascular interactions, but their functions in extravascular cell-cell communications is still debated. The roles of these two ligands in leukocyte trafficking, lymphocyte differentiation, and immunity to influenza infections were dissected in the present study. Surprisingly, double ICAM-1 and ICAM-2 knock out mice (herein ICAM-1/2-/- mice) infected with a lab adapted H1N1 influenza A virus fully recovered from infection, elicited potent humoral immunity, and generated normal long lasting anti-viral CD8+ T cell memory. Furthermore, lung capillary ICAMs were dispensable for both NK and neutrophil entry to virus infected lungs. Mediastinal lymph nodes (MedLNs) of ICAM-1/2-/- mice poorly recruited naïve T cells and B lymphocytes but elicited normal humoral immunity critical for viral clearance and effective CD8+ differentiation into IFN-γ producing T cells. Furthermore, whereas reduced numbers of virus specific effector CD8+ T cells accumulated inside infected ICAM-1/2-/- lungs, normal virus-specific TRM CD8+ cells were generated inside these lungs and fully protected ICAM-1/2-/- mice from secondary heterosubtypic infections. B lymphocyte entry to the MedLNs and differentiation into extrafollicular plasmablasts, producing high affinity anti-influenza IgG2a antibodies, were also ICAM-1 and ICAM-2 independent. A potent antiviral humoral response was associated with accumulation of hyper-stimulated cDC2s in ICAM null MedLNs and higher numbers of virus-specific T follicular helper (Tfh) cells generated following lung infection. Mice selectively depleted of cDC ICAM-1 expression supported, however, normal CTL and Tfh differentiation following influenza infection, ruling out essential co-stimulatory functions of DC ICAM-1 in CD8+ and CD4+ T cell differentiation. Collectively our findings suggest that lung ICAMs are dispensable for innate leukocyte trafficking to influenza infected lungs, for the generation of peri-epithelial TRM CD8+ cells, and long term anti-viral cellular immunity. In lung draining LNs, although ICAMs promote lymphocyte homing, these key integrin ligands are not required for influenza-specific humoral immunity or generation of IFN-γ effector CD8+ T cells. In conclusion, our findings suggest unexpected compensatory mechanisms that orchestrate protective anti-influenza immunity in the absence of vascular and extravascular ICAMs.